Semi-Invariant Submanifolds of Nearly Hyperbolic Cosymplectic Manifold (Global Journal of Science Frontier Research, 2013)
We consider a nearly hyperbolic cosymplectic manifold and study semi-invariant submanifolds of a nearly hyperbolic cosymplectic manifold. We also study parallel distributions on nearly hyperbolic cosymplectic manifold and find the integrability conditions of some distributions on nearly hyperbolic cosymplectic manifold.
Keywords: semi-invariant submanifolds; nearly hyperbolic cosymplectic manifold; intrgrability conditions; parallel distribution